1988
DOI: 10.1111/j.1745-4565.1988.tb00511.x
|View full text |Cite
|
Sign up to set email alerts
|

SPICES AND HERBS: THEIR ANTIMICROBIAL ACTIVITY AND ITS DETERMINATION1

Abstract: Throughout the years numerous investigations concerning the inhibition of microorganisms by spices, herbs, their extracts, essential oils and various constituents have been reported. Many of these materials possess significant antimicrobial activity, which in many cases is due primarily to a particular constituent. Interpretation and comparison of results of various studies is complicated by variations in the methodology used for the determination of antimicrobial activity. The antimicrobial activity varies de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
259
3
7

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 461 publications
(278 citation statements)
references
References 44 publications
9
259
3
7
Order By: Relevance
“…Various herbs and spices have been recognized for their antimicrobial activity and used throughout the past as an alternative approach to preserve foods. Inhibitory activity of herbs and derivatives on the growth of bacteria, fungi and microbial toxins has been well reported (Zaika 1988). Many plant essential oils of herbs are active against various food borne bacteria and molds (Aureli et al 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Various herbs and spices have been recognized for their antimicrobial activity and used throughout the past as an alternative approach to preserve foods. Inhibitory activity of herbs and derivatives on the growth of bacteria, fungi and microbial toxins has been well reported (Zaika 1988). Many plant essential oils of herbs are active against various food borne bacteria and molds (Aureli et al 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The antimicrobial properties vary depending on the concentration (Toroglu, Dıgrak, & Cenet, 2006). However, in other studies, ginger essential oil has been reported to have weak or no antimicrobial properties (Onyeagba, Ugbogu, Okeke, & Iroakasi, 2004;Wannissorn, Jarikasem, Siriwangchai, & Thubthimthed, 2005;Zaika, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Several spices, condiments, and plant extracts have strong medicinal, preservative, and antioxidant properties 1 . The antimicrobial activity of these ingredients is attributed to their essential oils, which are lipophilic and penetrate through the membrane to the interior of the cell and perform the inhibitory activity at the target site.…”
Section: Introductionmentioning
confidence: 99%
“…The antimicrobial activity of these ingredients is attributed to their essential oils, which are lipophilic and penetrate through the membrane to the interior of the cell and perform the inhibitory activity at the target site. Cinnamon effectively inhibits the growth of bacteria, although gram positive are more sensitive than gram negative 1 . During the past 30 years Escherichia coli in addition to other enteric pathogens, has emerged as one of the most important human diarrheal pathogens; several outbreaks of food-borne infections due to E. coli O157:H7 have been reported in different parts of the world, following consumption of unpasteurized apple cider and orange juices 2,3,4,5 .…”
Section: Introductionmentioning
confidence: 99%